H. pylori eradication did not improve dysregulation of specific oncogenic miRNAs in intestinal metaplastic glands - Shiotani, Akiko; Uedo, Noriya; Iishi, Hiroyasu; Murao, Takahisa; Kanzaki, Tomoko; Kimura, Yoshiki; Kamada, Tomoari; Kusunoki, Hiroaki; Inoue, Kazuhiko; Haruma, Ken (Journal of gastroenterology, 2012)
Background Many microRNAs (miRNAs) are differentially expressed in Helicobacter pylori -infected gastric mucosa and in gastric cancer tissue. Aim We aimed to compare the effect of H. pylori eradication on gastric mucosal miRNAs in subjects in a high-risk group for gastric cancer compared to controls. Methods Patients with a recent history of endoscopic resection for early gastric cancer and sex- and age-matched non-cancer controls were enrolled. The expression of 21 miRNAs was examined using gastric mucosal biopsy specimens and microdissected gastric glands from the lesser and greater curvatures of the gastric corpus both before and one year after H. pylori eradication. Results Twenty patients and 14 controls were enrolled. The expression of oncogenic miRNAs (miR-17/92 and the miR-106b-93-25 cluster, miR-21, miR-194, and miR-196) was significantly higher in the gastric mucosa of the cancer group than in the controls. H. pylori eradication resulted in a significant fall in the expression of oncogenic miRNAs only in the controls, whereas miR-223 expression was decreased and let-7d expression was increased in both groups. miR-196 was expressed only in intestinal metaplastic glands. The expression of oncogenic miRNAs was significantly higher in the intestinal metaplastic glands than in the non-intestinal metaplastic glands irrespective of H. pylori eradication. In neither group did H. pylori eradication significantly change any miRNA expression in the intestinal metaplastic glands. Conclusion Dysregulation of specific miRNAs is present in H. pylori -induced corpus gastritis. H. pylori eradication improved miRNA dysregulation, but not in intestinal metaplastic glands or in the gastric mucosa of patients in a high-risk group for gastric cancer.